Peran Komunikasi Organisasi Pada Pemerintahan Desa Sawo Dalam Implementasi Pendaftaran Tanah Sistematis Lengkap (PTSL) - Suroso (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Based on the people's need for land and houses, which are increasing day by day. The complete systematic land registration (PTSL) in the land office can carry out land tasks wherever the target of its activities is. The purpose of this study was to determine the implementation of the PTSL policy (complete systematic land registration) and to determine the factors affecting the implementation of the PTSL (Complete Systematic Land Registration) policy in Dukun District, Gresik Regency. This research uses descriptive qualitative research. The results showed that the implementation of the complete systematic land registration program (PTSL) policy in the village of Sawo, the sub-district of the Gresik district dukun is currently at the registration stage. So it cannot be said that the implementation of the PTSL (Complete Systematic Land Registration) policy was successful or not because it was still at the registration stage and the factors that influenced the PTSL (Complete Systematic Land Registration) policy in Sawo Village, Dukun District, Gresik Regency, were supporting factors that consists of a bureaucratic structure. While the inhibiting factor is communication (communications) and attitudes (dispositions or attitudes).